Immunodominant and Neutralizing Linear B-Cell Epitopes Spanning the Spike and Membrane Proteins of Porcine Epidemic Diarrhea Virus - Polyiam, Kanokporn; Ruengjitchatchawalya, Marasri; Mekvichitsaeng, Phenjun; Kaeoket, Kampon; Hoonsuwan, Tawatchai; Joiphaeng, Pichai; Roshorm, Yaowaluck Maprang (Frontiers in Immunology, 2022)
Porcine epidemic diarrhea virus (PEDV) is the causative agent of PED, an enteric disease that causes high mortality rates in piglets. PEDV is an alphacoronavirus that has high genetic diversity. Insights into neutralizing B cell epitopes of all genetically diverse PEDV strains are of importance, particularly for designing a vaccine that can provide broad protection against PEDV. In this work, we aimed to explore the landscape of linear B cell epitopes on the spike (S) and membrane (M) proteins of global PEDV strains. All amino acid sequences of the PEDV S and M proteins were retrieved from the NCBI database and grouped. Immunoinformatics-based methods were next developed and used to identify putative linear B cell epitopes from 14 and 5 consensus sequences generated from distinct groups of the S and M proteins, respectively. ELISA testing predicted peptides with PEDV-positive sera revealed 9 novel immunodominant epitopes on the S protein. Importantly, 7 of these novel immunodominant epitopes and other subdominant epitopes were demonstrated to be neutralizing epitopes by neutralization-inhibition assay. Our findings unveil important roles of the PEDV S2 subunit in both immune stimulation and virus neutralization. Additionally, our study shows the first time that M protein is also the target of PEDV neutralization with 7 neutralizing epitopes identified.. Conservancy profiles of the epitopes are also provided. In this study, we offer immunoinformatics-based methods for linear B cell epitope identification and a more complete profile of linear B cell epitopes across the PEDV S and M proteins, which may contribute to the development of a greater next generation PEDV vaccine as well as peptide-based immunoassays.